Analysis of the Risk of Work Accidents in High-Story Building Construction Projects using the FMEA (Failure Modes and Effects Analysis) Method - Meylinda Sabrinawati; I Nyoman Dita Pahang Putra (Formosa Journal of Multidisciplinary Research, 2024)
A construction project is a complex and exciting process, starting from planning and design, through to implementation and finishing. The process of building a construction project always has risks at every stage of its implementation. To prevent and minimize risks that could cause work accidents and losses on the project, it is necessary to carry out a work accident risk analysis on the project. This research carried out a work accident risk analysis on the Joint Lecture Building and FISIP Laboratory Phase 2 UPN "Veteran" East Java Construction Project using the FMEA method. The aim is to identify the risks of work accidents that could occur in building construction projects and to determine the severity level, incidence rate, detection level, and risk priority number (RPN) in these projects. The results of the research show that the risk of work accidents with the highest Risk Priority Number (RPN) value occurs in foundation structure work with the risk of workers being injured by these materials with RPN value of 174,857.14. Work on strengthening foundation structures with the highest RPN values requires the greatest attention and risk control measures.